On the identity of the Afrotropical species of Mallota Meigen (Diptera: Syrphidae) - De Meyer, M.; Goergen, G.; Midgley, J.M.; Jordaens, K. (2024)
The Afrotropical hoverflies belonging to the genus Mallota Meigen, 1822 (Diptera: Syrphidae) are revised. Ten species are recognized, of which four are new to science: Mallota glabra sp. nov., M. hircus sp. nov., M. wyatti sp. nov. and M. stipulata sp. nov. Merodon edentulus Macquart, 1855 is considered a junior synonym of Eristalis dasyops Wiedemann, 1819. Lectotypes are designated for Eristalis dasyops, Merodon edentulus, Mallota pachymera Bezzi, 1915 and Helophilus extremes Loew, 1858. The taxonomic history of the placement and identity of the different species of Mallota is presented. Their relationships, as well as affiliations with Afrotropical representatives of the genera Eristalis Latreille, 1804 and Myathropa Rondani, 1845, is briefly discussed based on morphological and DNA barcode data.